Instructional Leadership as a Vehicle for Teacher Collaboration and Student Achievement. What the German PISA 2015 Sample Tells Us - Mora-Ruano, Julio Gregorio; Schurig, Michael; Wittmann, Eveline (Frontiers in Education, 2021)
We investigated the effects of principal instructional leadership (IL) on the frequency of one form of teacher collaboration (TC) and their influence on student achievement (SA). Using data from the representative German PISA 2015 sample, we carry out structural equation modelling analysis to estimate the direct effects of IL on TC and of TC on SA, as well as the indirect effects of IL on SA. The analyses were conducted at the school level and only teachers belonging to the non-science group in PISA 2015 were included. Our analysis suggests that principal instructional leadership can positively influence teachers’ collaboration frequency and that the selected form of teacher collaboration is not positively related to student achievement. Our study builds on and extends research on student achievement by adding evidence about the relations between principal leadership and teacher collaboration in Germany.